Towards the fixation, storage and activation of carbon dioxide using iminodiacetic acid-based coordination compounds - O Toole, Annemarie (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
The main purpose of the current study was to expand, and fully explore, the library of known coordination compounds that form from the aqueous hpdta reaction system. The study examines the role hpdta coordination compounds play in the fixation of aerial carbon dioxide and their potential applications as catalysts in the reduction of carbon dioxide. Also considered is the potential application of hpdta based supramolecular assemblies as materials for gas storage and separation. The study uses 27Al, and 13C and 1H nuclear magnetic resonance (NMR) combined with electrospray ionisation mass spectrometry (ESI-MS- ) and Ultraviolet-visible (UV-Vis) spectroscopic analyses in order to gain insights into the solution behaviours of the Fe III and Al III hpdta based reaction system; Engages Gas-chromatography-mass spectrometry (GC-MS) headspace analyses coupled with ESI-MS in order to investigate the reversible fixation of atmospheric carbon dioxide using tetranuclear Fe III hpdta compounds; and employs cyclic voltammetry in combination with fluorescence spectrophotometry to establish the compounds' redox activities and electron scavenging characteristics. The research also applies the Sieverts Method to determine the gas storage capabilities and BET surface areas of novel {Al 15} hpdta supramolecular assemblies. The first chapter of this thesis outlines the specific aims of the research and introduces the reader to supramolecular chemistry and the applications of porous materials such as zeolites and metal-organic frameworks (MOF's) for gas storage and separation. Also considered is the use of transition metal complexes in the reduction of CO2.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.